Active ester resin containing epoxy group as well as preparation method and application of active ester resin
By using an epoxy group-containing reactive ester resin in the copper clad substrate resin, combined with addition polymerization of allyl groups and maleimide rings, the problem of insufficient dielectric properties and heat resistance of copper clad plates in the prior art is solved, and the preparation of high-performance copper clad plates is achieved.
Patent Information
- Application Number
- CN202411512643.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-28
AI Technical Summary
The existing copper clad substrate resin has high dielectric constant and dielectric loss, and has poor performance under high frequency and high temperature conditions, making it difficult to meet the needs of high-performance copper clad.
The reactive ester resin containing epoxy groups is used to enhance the heat resistance and dielectric properties of the cured epoxy resin, and is used as a toughener for a maleimide resin substrate through the addition polymerization of the allyl group in its structure and the maleimide ring.
It significantly reduces the dielectric loss and water absorption rate of copper clad plate, improves the dielectric constant and heat resistance, expands the application range of composite maleimide resin and epoxy resin, and meets the performance requirements under high frequency and high temperature conditions.
Smart Images

Figure BDA0005105853650000021 
Figure BDA0005105853650000101 
Figure BDA0005105853650000111
Abstract
Description
Technical Field
[0001] The present application relates to the field of synthetic resins for electronic material technology, and in particular to an active ester resin containing epoxy groups, and a preparation method and application thereof. Background Art
[0002] As a key component in the field of electronic communications, printed circuit boards (PCBs) are widely used in microwave communications, aerospace, medical equipment, industrial control and other industries. With the rapid development of high-frequency and high-speed communication technology, the market has put forward higher requirements on the performance of copper clad laminates used in PCBs. The performance of the matrix resin, which is the core material of copper clad laminates, directly affects the electrical, thermal and mechanical properties of copper clad laminates.
[0003] Traditional epoxy resin curing systems are widely used in copper clad laminates and are favored for their good mechanical properties and low cost. However, with the development of high-frequency and high-speed communication technology, the shortcomings of traditional epoxy resin curing systems have gradually become apparent. Traditional epoxy resin curing systems have high dielectric loss in the resin matrix due to the phenolic, anhydride or amine curing agents that produce highly polar secondary hydroxyl and amine residues when curing epoxy, resulting in more serious signal loss in high-frequency applications. At the same time, their heat resistance level is low, and they cannot meet the current high-performance copper clad laminates' requirements for high frequency, high temperature and other harsh conditions.
[0004] Bismaleimide resin has become one of the most competitive resins in the current high-performance copper-clad laminate substrates due to its excellent thermal stability, excellent dielectric properties and corrosion resistance, as well as simple molding process and no release of small molecules during the curing process. However, the cured network structure of bismaleimide resin self-polymer is dense, the cross-linking density is high, and the rigidity of bismaleimide molecules is strong, resulting in its greater brittleness and poor toughness. Therefore, it is usually necessary to modify and toughen it to meet the actual application requirements. In the existing toughening modification technology, allyl compounds are widely regarded as an effective toughening agent. Allyl groups can react with maleimide groups through an "ENE" addition reaction to form a prepolymer, which then undergoes a Diels-Alder cyclization reaction with the imide ring at a higher temperature and forms a tough polymer with a high degree of cross-linking through anionic imide polymerization. Diallyl bisphenol A is currently the most commonly used allyl compound, but the strong polarity of its terminal hydroxyl group leads to an increase in the dielectric constant and dielectric loss of the cured material, which makes it difficult to meet the requirements of high-frequency application fields for copper clad laminate materials.
[0005] Compounding epoxy resin with bismaleimide resin to obtain better dielectric and heat resistance than epoxy resin curing system is one of the ways to improve the performance of PCB substrate in the industry. However, the molecular structure of bismaleimide and epoxy resin is quite different, and the poor compatibility of resin leads to problems such as delamination and precipitation during lamination curing, which limits the application of the epoxy / bismaleimide compounding method. CN118479996A provides an active ester maleimide resin containing allyl group, which can be used as a low polar toughening agent to toughen bismaleimide. At the same time, due to the presence of ester group with reactive activity with epoxy, it can react with epoxy, increasing the mechanism of co-curing of maleimide resin and epoxy resin. Its structure determines that the molecular rigidity of this resin is similar to that of maleimide resin. Although it can increase the compound application of maleimide resin and epoxy to a certain extent, its applicability is relatively narrow. When used in combination with more types of epoxy resins to make copper clad laminates, there is still a phenomenon of inhomogeneous precipitation of resin in the semi-curing stage, resulting in delamination and explosion of the substrate during lamination or soldering, which greatly limits the selection of epoxy resin. Summary of the invention
[0006] The present application provides an active ester resin containing epoxy groups and a preparation method and application thereof, so as to solve the technical problems in the prior art that the modified matrix resin of copper clad laminate has high dielectric constant and dielectric loss and narrow application range.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] An active ester resin containing epoxy groups has the following structural formula:
[0009]
[0010] Among them, R is Any of the following;
[0011] R1 is Any of the following;
[0012] R2 is =Any one of;
[0013] n is any integer from 1 to 10.
[0014] The present invention provides an active ester resin structure containing epoxy groups without polar hydroxyl groups, compared to the traditional phenolic curing agent, anhydride curing agent, amine curing agent with more polar groups in the molecule, overcomes the problems of poor dielectric properties and high water absorption caused by the introduction of its polar groups. In addition, the structure contains allyl groups, and under high temperature conditions, the addition polymerization of the allyl group in the structure and the maleimide ring can introduce the maleimide ring into the epoxy resin system, further enhancing the heat resistance and dielectric properties of epoxy resin cured product. Further, the prepared active ester resin containing epoxy groups is used as a toughening agent for high cross-linking density maleimide resin substrates, which greatly reduces the problem of reduced dielectric properties of maleimide resin substrates caused by the polar hydroxyl groups introduced during the toughening of traditional diallyl bisphenol A.
[0015] In addition, the present invention also provides a method for preparing an active ester resin containing an epoxy group, comprising the following steps:
[0016] S1. In a four-mouth reactor equipped with nitrogen, stirring, and a reflux condenser, add the acyl chloride compound, diallyl bisphenol A, a blocking agent, and solvent A in sequence and stir to dissolve;
[0017] S2, cooling the mixture in the reactor to room temperature, adding the acid binding agent dropwise to the reactor in a water bath within 1 to 3 hours, and after the addition is complete, heating to 50 to 80° C. and reacting for 1 to 4 hours;
[0018] S3. After the reaction is completed, the reacted materials in the reactor are filtered, washed with water until pH=7, cooled to a temperature ≤50°C, formic acid is added to the reactor, and hydrogen peroxide is added dropwise to the reactor within 1 to 2 hours. After the addition is completed, the reaction is kept warm at 30 to 70°C for 2 to 4 hours.
[0019] S4. After the reaction is completed, the reacted material in the reactor is filtered, washed with water until the pH value is 7, and then the solvent is evaporated under reduced pressure to obtain an active ester resin containing epoxy groups.
[0020] As some possible implementation methods of the present application, the acid binding agent is any one of triethylamine, trimethylamine, pyridine, sodium carbonate, potassium carbonate, and potassium hydroxide; the solvent A is any one or more of toluene, xylene, butanone, methyl isobutyl ketone, and cyclopentane.
[0021] As some possible implementation methods of the present application, the molar ratio of the acyl chloride compound, diallyl bisphenol A, capping agent, formic acid, and hydrogen peroxide is 1: (0.5-0.91): (0.18-1): (0.25-1.3): (0.25-1.3). As some possible implementation methods of the present application, the molar amount of the acid binding agent is 1.03-1.05 times the molar amount of the acyl chloride compound.
[0022] In addition, the present invention also provides an application of an active ester resin containing epoxy groups in the preparation of a high-toughness, high-heat-resistant, low-dielectric copper-clad laminate.
[0023] As some possible implementation methods of the present application, the present invention provides the following two methods for preparing dielectric copper clad laminates, the first method of preparing the dielectric copper clad laminate is as follows:
[0024] S1. 100 parts by mass of epoxy resin, 50 to 70 parts by mass of active ester resin containing epoxy groups, 30 to 60 parts by mass of filler, and 0.1 to 0.5 parts by mass of accelerator are uniformly mixed in an organic solvent to prepare a prepreg having a solid content of 65% ± 1%;
[0025] S2, firstly impregnating the glass fiber cloth in the prepreg, and then baking the glass fiber cloth impregnated with the resin glue at a temperature of 150° C. to 200° C. for 1 to 6 minutes to obtain a prepreg;
[0026] S3. Stack the semi-cured sheets according to the required number of layers and attach copper foil on both sides, place them in a vacuum hot press, increase the temperature from room temperature to 160°C at a heating rate of 3°C / min, increase the pressure from 0.2MPa to 4MPa at a rate of 0.1MPa / 1min, evacuate to less than 80torr, keep pressing for 0.5-1h, then heat to 195-240°C and keep constant pressure for 3-5h, release the pressure and cool naturally to obtain a high heat-resistant, low dielectric copper clad laminate.
[0027] In this scheme, active ester resin containing epoxy groups is used as the main raw material of copper clad laminate and as epoxy resin curing agent, which overcomes the problems of poor dielectric properties and high water absorption caused by the presence of more polar groups remaining after curing epoxy with traditional epoxy curing agents. The obtained copper clad laminate has good performance parameters: dielectric constant Dk is 3.20-3.40 at 10GHz, dielectric loss Df is 0.007-0.0075, and water absorption is 0.2%-0.3%.
[0028] The second preparation method is as follows:
[0029] S1, 50 parts by mass of bismaleimide resin, 32-45 parts by mass of active ester resin containing epoxy group, 45-65 parts by mass of epoxy resin, 30-60 parts by mass of filler, and 0.1-0.5 parts by mass of accelerator are uniformly mixed in an organic solvent to prepare a prepreg with a solid content of 65%±1%;
[0030] S2, firstly impregnating the glass fiber cloth in the prepreg, and then baking the glass fiber cloth impregnated with the resin glue at a temperature of 150° C. to 200° C. for 1 to 6 minutes to obtain a prepreg;
[0031] S3, stack the semi-cured sheets according to the required number of layers and attach copper foil on both sides, place them in a vacuum hot press, heat them from room temperature to 180°C at a heating rate of 3°C / min, increase the pressure from 0.2MPa to 4MPa at a rate of 0.1MPa / 1min, evacuate to within 80torr, keep pressing for 0.5-1h, then heat them to 185-240°C and keep constant pressure for 3-5h, release the pressure and cool naturally to obtain a high-toughness, high-heat-resistant and low-dielectric copper-clad laminate
[0032] In this scheme, the active ester resin containing epoxy groups is used as the main raw material of the copper clad laminate, and is compounded with epoxy resin and bismaleimide resin. It has good compatibility and will not delaminate. The technical parameters of the copper clad laminate prepared are as follows: bending strength 220.0MPa~310.0MPa, bending modulus 20.0GPa~30.0GPa, glass transition temperature Tg 200℃~221℃, dielectric constant Dk of 3.30~3.55 at 10GHz, and dielectric loss Df of 0.005~0.006.
[0033] As some feasible embodiments of the present application, the bismaleimide resin in the second method is a compound with maleimide rings at both ends, specifically any one of bis(3-ethyl-5-methyl-4-maleimidephenyl)methane, bis(3,5-diethyl-4-maleimidephenyl)methane, bis(4-maleimidephenyl)methane, bis(3,5-dimethyl-4-maleimidephenyl)methane, 2,2'-bis[4-(4-maleimidephenoxy)phenyl]propane, diphenylmethane bismaleimide, and 2,2'-N,N'-m-phenylene bismaleimide.
[0034] As some possible implementation methods of the present application, the epoxy resin in the second method is any one or more of dicyclopentadiene phenol epoxy resin, bisphenol A formaldehyde novolac epoxy resin, phenol formaldehyde novolac epoxy resin, and o-cresol novolac epoxy resin.
[0035] As some feasible implementation methods of the present application, the accelerator in the preparation methods of the above two copper clad laminates is any one of 2,4,6-tris(dimethylaminomethyl)phenol (DMP-30 for short), triphenylphosphine (TPP for short), 4-dimethylaminopyridine, 2-methylimidazole, and 1-benzyl-2-methylimidazole; the filler is any one of silica, montmorillonite, magnesium oxide, aluminum oxide, mica powder, etc.; the organic solvent is any one of acetone, butanone, methyl isobutyl ketone, toluene, propylene glycol monomethyl ether, and ethylene glycol methyl ether; the glass fiber cloth model is any one of 1080E, 2116, 2313, 3313, and 7628.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] (1) The active ester resin containing epoxy groups synthesized by the present invention has no polar hydroxyl groups in its structure. Compared with traditional phenolic curing agents, acid anhydride curing agents, and amine curing agents having more polar groups in their molecules, it overcomes the problems of poor dielectric properties and high water absorption caused by the introduction of polar groups, and can give epoxy resin cured products good dielectric properties. The resulting copper clad laminate has good performance parameters.
[0038] (2) The active ester resin containing epoxy groups synthesized by the present invention contains allyl groups in its structure. Under high temperature conditions, the addition polymerization of the allyl groups in the structure and the maleimide ring can introduce the maleimide ring into the epoxy resin system, further enhancing the heat resistance of the epoxy resin cured product.
[0039] (3) The active ester resin containing epoxy groups synthesized by the present invention has a wide range of uses. In addition to being used as an epoxy resin curing agent, it can also be applied to bismaleimide matrix resins and used alone as a toughening agent for high cross-link density maleimide resin substrates. Compared with traditional diallyl bisphenol A toughening, while ensuring the toughening effect, the dielectric properties of the maleimide resin substrate caused by the polar hydroxyl groups introduced by diallyl bisphenol A can be greatly reduced. At the same time, the resin contains epoxy groups, which can be introduced into the maleimide curing system to increase the compatibility with epoxy resins, thereby expanding the composite application range of maleimide resins and epoxy resins.
[0040] (4) The product of the present invention has a simple preparation process, is easy to operate, and has strong practicability. DETAILED DESCRIPTION
[0041] Example 1
[0042] A method for preparing an active ester resin containing an epoxy group comprises the following steps:
[0043] S1. In a four-necked reactor (bottle) equipped with nitrogen, stirring, and a reflux condenser, 1 mol of 2,2'-biphenyl dicarboxylic acid chloride, 0.5 mol of diallyl bisphenol A, 1 mol of α-naphthol, and 1500 g of a mixed solvent (toluene: cyclopentane = 3:1) were added in sequence and stirred to dissolve;
[0044] S2, cool to room temperature, add 2.03 mol of triethylamine dropwise to the reactor (bottle) in a water bath within 2 hours, and after the addition is complete, heat to 55°C and react for 3 hours;
[0045] S3. After the reaction is completed, the reaction material is filtered, washed with water to pH = 7, cooled to 40°C, 0.5 mol of formic acid is added to the reactor, and 0.5 mol of hydrogen peroxide is added dropwise to the reactor within 1 hour. After the addition is completed, the temperature is raised to 45°C and kept warm for 4 hours.
[0046] S4. After the reaction is completed, the reacted material in the reactor is filtered, washed with water until the pH value is 7, and the solvent is evaporated under reduced pressure to obtain an active ester resin containing epoxy groups. It is found through testing that the ester equivalent of the resin is 245 g / mol and the epoxy equivalent is 480 g / mol.
[0047] Example 2
[0048] A method for preparing an active ester resin containing an epoxy group comprises the following steps:
[0049] S1. In a four-necked reactor (bottle) equipped with nitrogen, stirring, and a reflux condenser, 1 mol of 4,4'-biphenyl dicarboxylic acid chloride, 0.67 mol of diallyl bisphenol A, 0.67 mol of phenol, and 1300 g of a mixed solvent (toluene:DMF=4:1) were added in sequence and stirred to dissolve;
[0050] S2, cool to room temperature, add 2.05 mol of triethylamine dropwise to the reactor (bottle) in a water bath within 2 hours, and after the addition is complete, heat to 55°C and react for 3 hours;
[0051] S3. After the reaction is completed, the reaction material is filtered, washed with water to pH = 7, cooled to 40°C, 1 mol of formic acid is added to the reactor, and 1 mol of hydrogen peroxide is added dropwise to the reactor within 1.5 hours. After the addition is completed, the temperature is raised to 45°C and kept warm for 4 hours.
[0052] S4. After the reaction is completed, the reacted material in the reactor is filtered, washed with water until the pH value is 7, and the solvent is evaporated under reduced pressure to obtain an active ester resin containing epoxy groups. The test shows that the ester equivalent of the resin is 252 g / mol, and the epoxy equivalent is 319 g / mol.
[0053] Example 3
[0054] A method for preparing an active ester resin containing an epoxy group comprises the following steps:
[0055] S1. In a four-necked reactor (bottle) equipped with nitrogen, stirring, and a reflux condenser, 1 mol of isophthaloyl chloride, 0.75 mol of diallyl bisphenol A, 0.5 mol of β-naphthol, and 1200 g of toluene were added in sequence and stirred to dissolve;
[0056] S2, cool to room temperature, add 2.03 mol of pyridine dropwise to the reactor (bottle) in a water bath within 3 hours, and after the addition is complete, heat to 45°C and react for 4 hours;
[0057] S3. After the reaction is completed, the reaction material is filtered, washed with water to pH = 7, cooled to 40°C, 1 mol of formic acid is added to the reactor, and 1 mol of hydrogen peroxide is added dropwise to the reactor within 1.5 hours. After the addition is completed, the temperature is raised to 45°C and kept warm for 4 hours.
[0058] S4. After the reaction is completed, the reacted material in the reactor is filtered, washed with water until the pH value is 7, and the solvent is evaporated under reduced pressure to obtain an active ester resin containing epoxy groups. The test results show that the ester equivalent is 258 g / mol and the epoxy equivalent is 306 g / mol.
[0059] Embodiments 4 to 6
[0060] The preparation method of the high heat-resistant low dielectric copper clad laminate specifically comprises the following steps:
[0061] S1, 100 parts by mass of epoxy resin, 48-56 parts by mass of active ester resin containing epoxy groups prepared in Examples 1 to 3, 49-52 parts by mass of filler, and 0.2-0.3 parts by mass of accelerator are uniformly mixed in an organic solvent to prepare a prepreg having a solid content of 65%±1% (the mass percentage content of the sum of epoxy resin, active ester resin containing epoxy groups and filler);
[0062] S2, firstly impregnating the glass fiber cloth in the prepreg, and then baking the glass fiber cloth impregnated with the resin glue at a temperature of 150° C. to 200° C. for 1 to 6 minutes to obtain a prepreg;
[0063] S3. Stack the semi-cured sheets according to the required number of layers (6 layers) and attach copper foil on both sides, place them in a vacuum hot press, increase the temperature from room temperature to 160°C at a heating rate of 3°C / min, increase the pressure from 0.2MPa to 4MPa at a rate of 0.1MPa / 1min, evacuate to less than 80torr, keep pressing for 0.5-1h, then heat to 195-240°C and maintain constant pressure for 3-5h, release the pressure and cool naturally to obtain a high heat-resistant, low dielectric copper clad laminate.
[0064] Embodiments 7 to 9
[0065] The preparation method of the high-toughness, high-heat-resistant and low-dielectric copper-clad laminate specifically comprises the following steps:
[0066] S1, 50-100 parts by mass of bismaleimide resin, 20-60 parts by mass of active ester resin containing epoxy groups prepared in Examples 1 to 3, 0-65 parts by mass of epoxy resin, 30-60 parts by mass of filler, and 0.1-0.5 parts by mass of accelerator are uniformly mixed in an organic solvent to prepare a prepreg having a solid content of 65% ± 1% (the mass percentage content of the sum of epoxy resin, active ester resin containing epoxy groups and filler);
[0067] S2, firstly impregnating the glass fiber cloth in the prepreg, and then baking the glass fiber cloth impregnated with the resin glue at a temperature of 150° C. to 200° C. for 1 to 6 minutes to obtain a prepreg;
[0068] S3. Stack the semi-cured sheets according to the required number of layers (6 layers) and attach copper foil on both sides, place them in a vacuum hot press, raise the temperature from room temperature to 180°C at a heating rate of 3°C / min, increase the pressure from 0.2MPa to 4MPa at a rate of 0.1MPa / 1min, evacuate to less than 80torr, keep pressing for 0.5-1h, then raise the temperature to 185-240°C and maintain constant pressure for 3-5h, release the pressure and cool naturally to obtain a high-toughness, high-heat-resistant and low-dielectric copper-clad laminate.
[0069] Example 10
[0070] The preparation method of the high heat-resistant low dielectric copper clad laminate specifically comprises the following steps:
[0071] S1, 59 parts by mass of diphenylmethane bismaleimide resin, 60 parts by mass of active ester resin containing epoxy group prepared in Example 3, 42 parts by mass of naphthalene epoxy resin, 53 parts by mass of silica, 0.40 parts by mass of 2-methylimidazole, and 115 parts by mass of butanone are uniformly mixed to prepare a prepreg having a solid content of 65% (the mass percentage content of the sum of bismaleimide resin, epoxy resin, main chain allyl active ester type imide resin and filler);
[0072] S2, firstly impregnating the glass fiber cloth in the prepreg, and then baking the glass fiber cloth impregnated with the resin glue at 180° C. for 5 minutes to obtain a prepreg;
[0073] S3. Stack 10 layers of prepreg and attach copper foil on both sides, place them in a vacuum hot press, raise the temperature from room temperature to 180°C at a heating rate of 3°C / min, increase the pressure from 0.2MPa to 4MPa at a rate of 0.1MPa / 1min, evacuate to less than 80torr, keep pressing for 1h, then raise the temperature to 220°C and keep constant pressure for 4h, release the pressure and cool naturally, thus making comparative 5 copper clad laminate.
[0074] Comparative Example 1
[0075] The method for preparing a low dielectric copper clad laminate specifically comprises the following steps:
[0076] S1, 100 weight parts of o-cresol epoxy resin, 26 weight parts of phenolic curing agent, 50 weight parts of mica powder, and 0.22 weight parts of TPP are uniformly mixed in 95 weight parts of butanone to prepare a prepreg with a solid content of 65% (the weight percentage content of the sum of epoxy resin, active ester curing agent and filler);
[0077] S2, then firstly impregnate the glass fiber cloth in the prepreg, and then bake the glass fiber cloth impregnated with the resin glue at 150° C. for 5 minutes to obtain a prepreg;
[0078] S3. Stack 10 layers of prepregs and attach copper foil on both sides, place them in a vacuum hot press, raise the temperature from room temperature to 160°C at a heating rate of 3°C / min, increase the pressure from 0.2MPa to 4MPa at a rate of 0.1MPa / 1min, evacuate to less than 80torr, keep pressing for 1h, then raise the temperature to 230°C and keep constant pressure for 4h, release the pressure and cool naturally, that is, the copper clad laminate of Comparative Example 1.
[0079] Comparative Example 2
[0080] The method for preparing a low dielectric copper clad laminate specifically comprises the following steps:
[0081] S1. 100 parts by mass of bisphenol A formaldehyde novolac epoxy resin, 31 parts by mass of phenol novolac curing agent, 52 parts by mass of mica powder, and 0.23 parts by mass of TPP are uniformly mixed in 95 parts by mass of butanone to prepare a prepreg with a solid content of 65% (the mass percentage content of the sum of epoxy resin, active ester curing agent and filler);
[0082] S2, firstly impregnating the glass fiber cloth in the prepreg, and then baking the glass fiber cloth impregnated with the resin glue at 160° C. for 4 minutes to obtain a prepreg;
[0083] S3. Stack 10 layers of prepregs and attach copper foil on both sides, place them in a vacuum hot press, raise the temperature from room temperature to 175°C at a heating rate of 3°C / min, increase the pressure from 0.2MPa to 4MPa at a rate of 0.1MPa / 1min, evacuate to less than 80torr, keep pressing for 1h, then raise the temperature to 230°C and keep constant pressure for 4h, release the pressure and cool naturally, that is, the copper clad laminate of Comparative Example 2.
[0084] Comparative Example 3
[0085] The method for preparing a low dielectric copper clad laminate specifically comprises the following steps:
[0086] S1. 100 parts by mass of dicyclopentadiene phenol epoxy resin, 29 parts by mass of phenol novolac curing agent, 51 parts by mass of mica powder, and 0.23 parts by mass of TPP are uniformly mixed in 98 parts by mass of butanone to prepare a prepreg having a solid content of 65% (the mass percentage content of the sum of epoxy resin, active ester curing agent and filler);
[0087] S2, then firstly impregnate the glass fiber cloth in the prepreg, and then bake the glass fiber cloth impregnated with the resin glue at 150° C. for 5 minutes to obtain a prepreg;
[0088] S3. Stack 10 layers of prepregs and attach copper foil on both sides, place them in a vacuum hot press, raise the temperature from room temperature to 180°C at a heating rate of 3°C / min, increase the pressure from 0.2MPa to 4MPa at a rate of 0.1MPa / 1min, evacuate to less than 80torr, keep pressing for 1h, then raise the temperature to 230°C and keep constant pressure for 4h, release the pressure and cool naturally, that is, Comparative Example 3 copper clad laminate.
[0089] Comparative Example 4
[0090] The preparation method of the high heat-resistant low dielectric copper clad laminate specifically comprises the following steps:
[0091] S1, 100 parts by mass of diphenylmethane bismaleimide resin, 47 parts by mass of silica, and 0.4 parts by mass of accelerator are uniformly mixed in 80 parts by mass of butanone to prepare a prepreg with a solid content of 65% (the mass percentage content of the sum of the resin and the filler);
[0092] S2, then firstly impregnating the glass fiber cloth in the prepreg, and then baking the glass fiber cloth impregnated with the resin glue at a temperature of 150° C. for 6 minutes to obtain a prepreg;
[0093] S3. Stack 10 layers of prepregs and attach copper foil on both sides, place them in a vacuum hot press, raise the temperature from room temperature to 180°C at a heating rate of 3°C / min, increase the pressure from 0.2MPa to 4MPa at a rate of 0.1MPa / 1min, evacuate to less than 80torr, keep pressing for 2h, then raise the temperature to 220°C and keep constant pressure for 3h, release the pressure and cool naturally, that is, the copper clad laminate of Comparative Example 4.
[0094] Comparative Example 5
[0095] The preparation method of the high-toughness, high-heat-resistant and low-dielectric copper-clad laminate specifically comprises the following steps:
[0096] S1. 100 parts by mass of diphenylmethane bismaleimide resin, 15 parts by mass of diallyl bisphenol A, 48 parts by mass of silicon dioxide, 0.32 parts by mass of 2-methylimidazole, and 88 parts by mass of butanone are uniformly mixed to prepare a prepreg having a solid content of 65% (the mass percentage content of the sum of bismaleimide resin, diallyl bisphenol A and filler);
[0097] S2, firstly impregnating the glass fiber cloth in the prepreg, and then baking the glass fiber cloth impregnated with the resin glue at 180° C. for 5 minutes to obtain a prepreg;
[0098] S3. Stack 10 layers of prepreg and attach copper foil on both sides, place them in a vacuum hot press, raise the temperature from room temperature to 180°C at a heating rate of 3°C / min, increase the pressure from 0.2MPa to 4MPa at a rate of 0.1MPa / 1min, evacuate to less than 80torr, keep pressing for 1h, then raise the temperature to 220°C and keep constant pressure for 4h, release the pressure and cool naturally, thus making comparative 5 copper clad laminate.
[0099] Comparative Example 6
[0100] A method for preparing an imide resin containing an active ester of allyl groups in the main chain comprises the following steps:
[0101] S1. In a four-necked reactor (bottle) equipped with nitrogen, stirring, and a reflux condenser, 1 mol of isophthaloyl chloride, 0.75 mol of diallyl bisphenol A, 0.5 mol of 4-maleimidophenol, and 1200 g of a mixed solvent (toluene: butanone = 4:3) were added in sequence and stirred to dissolve;
[0102] S2, cool to room temperature, add 2.03 mol of pyridine dropwise to the reactor (bottle) in a water bath within 3 hours, and after the addition is complete, heat to 45°C and react for 4 hours;
[0103] S3. After the reaction is completed, the reaction material is filtered, washed with water until the pH value is 7, and the solvent is evaporated under reduced pressure to obtain an imide resin containing an active ester of allyl group. The ester equivalent is 264 g / mol.
[0104] Comparative Examples 7 to 8
[0105] The method for preparing a low dielectric copper clad laminate specifically comprises the following steps:
[0106] S1, 28-59 parts by weight of diphenylmethane bismaleimide resin, 62 parts by weight of main chain allyl active ester imide resin prepared in Comparative Example 6, 42 parts by weight of naphthalene epoxy resin, 43-54 parts by weight of silica, 0.29-0.41 parts by weight of 2-methylimidazole, and 94-117 parts by weight of butanone are uniformly mixed to prepare a prepreg having a solid content of 65% (the sum of the mass percentage of bismaleimide resin, epoxy resin, main chain allyl active ester imide resin and filler);
[0107] S2, firstly impregnating the glass fiber cloth in the prepreg, and then baking the glass fiber cloth impregnated with the resin glue at 180° C. for 5 minutes to obtain a prepreg;
[0108] S3. Stack 10 layers of prepreg and attach copper foil on both sides, place them in a vacuum hot press, raise the temperature from room temperature to 180°C at a heating rate of 3°C / min, increase the pressure from 0.2MPa to 4MPa at a rate of 0.1MPa / 1min, evacuate to less than 80torr, keep pressing for 1h, then raise the temperature to 220°C and keep constant pressure for 4h, release the pressure and cool naturally, thus making comparative 5 copper clad laminate.
[0109] Table 1 is a table of the composition ratios and performance parameters of various raw material components of Examples 4 to 6 of high heat-resistant low dielectric copper clad laminates, and the units of component usage in the table are parts by mass.
[0110] Table 1:
[0111]
[0112]
[0113] A1: the active ester resin containing epoxy groups prepared in Example 1;
[0114] A2: the active ester resin containing epoxy groups obtained in Example 2;
[0115] A3: the active ester resin containing epoxy groups obtained in Example 3;
[0116] B1: o-cresol novolac epoxy resin;
[0117] B2: bisphenol A formaldehyde novolac epoxy resin;
[0118] B3: dicyclopentadiene phenol epoxy resin.
[0119] The data in Table 1 show that the copper-clad laminates prepared in Examples 4 to 6 have lower dielectric constants (Dk), dielectric losses (Df), water absorption, and higher heat resistance (Tg) than the copper-clad laminates prepared in Comparative Examples 1 to 3.
[0120] Table 2 is a table of the proportions and performance parameters of the raw material components of Examples 7 to 9 of the high-toughness, high-heat-resistant and low-dielectric copper-clad laminates. The units of the component amounts in the table are parts by mass.
[0121] Table 2:
[0122]
[0123] In the table:
[0124] A1: the active ester resin containing epoxy groups prepared in Example 1;
[0125] A2: the active ester resin containing epoxy groups obtained in Example 2;
[0126] A3: The active ester resin containing epoxy groups prepared in Example 3.
[0127] The data in Table 2 show that: compared with Comparative Example 4, Examples 7 to 9 have significantly better flexural strength and flexural modulus, and the resin of the present invention can effectively toughen the maleimide resin; compared with Comparative Example 5, Examples 7 to 9 have lower dielectric loss, and are at the same level as the data of the untoughened Example 4. Compared with diallyl bisphenol A, the resin of the present invention can effectively maintain the dielectric properties of the cured product when toughening the maleimide resin.
[0128] Table 3 is a table of the proportions and performance parameters of various raw material components of Example 10 of the high heat-resistant and low-dielectric copper-clad laminate, and the units of component usage in the table are parts by mass.
[0129] Table 3
[0130]
[0131] In the table:
[0132] A3: the active ester resin containing epoxy groups obtained in Example 3;
[0133] C1: Comparative Example 6 obtains an imide resin containing active ester of allyl group in the main chain.
[0134] The data in Table 3 show that when the resin of the present invention is compounded with naphthalene-type epoxy resin and diphenylmethane bismaleimide, the obtained resin can have a higher heat crack resistance time compared with the resin prepared in Comparative Example 6, and its cured product has higher heat resistance and better compatibility of the resin in the formula.
[0135] Related experiments: Glass transition temperature Tg: Determined by dynamic thermomechanical analysis (DMA) according to the DMA method specified in 2.4.24.4 of IPC-TM-650;
[0136] Dielectric constant Dk and dielectric loss Df: Use SPDR method to test 10GHz data according to the method specified in IEC 61189-2-721;
[0137] Bending strength and bending modulus: three-point bending performance test is adopted, and the test is carried out in accordance with GB / T 14452-1993 standard;
[0138] Water absorption test: Tested in accordance with GB / T 1034-2008 standard;
[0139] Thermal crack resistance time (T288): Tested using thermomechanical analysis (TMA) according to the T288 method specified in 3.10.1.12 of IPC-401B.
Claims
1. An active ester resin containing epoxy groups, characterized in that: The structural formula is as follows: Among them, R is Any of the following: R1 is Any of the following: R2 is Any of the following: n is any integer from 1 to 10.
2. The method for preparing an active ester resin containing epoxy groups according to claim 1, characterized in that: The steps include: S1. In a four-mouth reactor equipped with nitrogen, stirring, and a reflux condenser, add the acyl chloride compound, diallyl bisphenol A, a blocking agent, and solvent A in sequence and stir to dissolve; S2, cooling the mixture in the reactor to room temperature, adding the acid binding agent dropwise to the reactor in a water bath within 1 to 3 hours, and after the addition is complete, heating to 50 to 80° C. and reacting for 1 to 4 hours; S3. After the reaction is completed, the reacted materials in the reactor are filtered, washed with water until pH=7, cooled to a temperature ≤50°C, formic acid is added to the reactor, and hydrogen peroxide is added dropwise to the reactor within 1 to 2 hours. After the addition is completed, the reaction is kept warm at 30 to 70°C for 2 to 4 hours. S4. After the reaction is completed, the reacted material in the reactor is filtered, washed with water until the pH value is 7, and then the solvent is evaporated under reduced pressure to obtain an active ester resin containing epoxy groups.
3. The method for preparing an active ester resin containing epoxy groups according to claim 2, characterized in that: The molar ratio of the acyl chloride compound, diallyl bisphenol A, the end-capping agent, formic acid and hydrogen peroxide is 1: (0.5-0.91): (0.18-1): (0.25-1.3): (0.25-1.3).
4. The method for preparing an active ester resin containing epoxy groups according to claim 2, characterized in that: The molar amount of the acid binding agent is 1.03 to 1.05 times the molar amount of the acyl chloride compound.
5. Use of an active ester resin containing epoxy groups according to claim 1 in the preparation of high-toughness, high-heat-resistant, low-dielectric copper-clad laminates.
6. The use of an active ester resin containing epoxy groups according to claim 5 in the preparation of a high-toughness, high-heat-resistant, low-dielectric copper-clad laminate, characterized in that: The preparation method of the dielectric copper clad laminate is as follows: S1. 100 parts by mass of epoxy resin, 50 to 70 parts by mass of active ester resin containing epoxy groups, 30 to 60 parts by mass of filler, and 0.1 to 0.5 parts by mass of accelerator are uniformly mixed in an organic solvent to prepare a prepreg having a solid content of 65% ± 1%; S2, firstly impregnating the glass fiber cloth in the prepreg, and then baking the glass fiber cloth impregnated with the resin glue at a temperature of 150° C. to 200° C. for 1 to 6 minutes to obtain a prepreg; S3. Stack the semi-cured sheets according to the required number of layers and attach copper foil on both sides, place them in a vacuum hot press, increase the temperature from room temperature to 160°C at a heating rate of 3°C / min, increase the pressure from 0.2MPa to 4MPa at a rate of 0.1MPa / 1min, evacuate to less than 80torr, keep pressing for 0.5-1h, then heat to 195-240°C and keep constant pressure for 3-5h, release the pressure and cool naturally to obtain a high heat-resistant, low dielectric copper clad laminate.
7. The use of an active ester resin containing epoxy groups according to claim 5 in the preparation of a high-toughness, high-heat-resistant, low-dielectric copper-clad laminate, characterized in that: The preparation method of the dielectric copper clad laminate is as follows: S1, 50 parts by mass of bismaleimide resin, 32-45 parts by mass of active ester resin containing epoxy group, 45-65 parts by mass of epoxy resin, 30-60 parts by mass of filler, and 0.1-0.5 parts by mass of accelerator are uniformly mixed in an organic solvent to prepare a prepreg with a solid content of 65%±1%; S2, firstly impregnating the glass fiber cloth in the prepreg, and then baking the glass fiber cloth impregnated with the resin glue at a temperature of 150° C. to 200° C. for 1 to 6 minutes to obtain a prepreg; S3. Stack the semi-cured sheets according to the required number of layers and attach copper foil on both sides, place them in a vacuum hot press, raise the temperature from room temperature to 180°C at a heating rate of 3°C / min, increase the pressure from 0.2MPa to 4MPa at a rate of 0.1MPa / 1min, evacuate to less than 80torr, keep pressing for 0.5-1h, then raise the temperature to 185-240°C and maintain constant pressure for 3-5h, release the pressure and cool naturally to obtain a high-toughness, high-heat-resistant and low-dielectric copper-clad laminate.
8. The use of an active ester resin containing epoxy groups according to claim 7 in the preparation of a high-toughness, high-heat-resistant, low-dielectric copper-clad laminate, characterized in that: The epoxy resin is any one or more of dicyclopentadiene phenol epoxy resin, bisphenol A formaldehyde novolac epoxy resin, phenol formaldehyde novolac epoxy resin, and o-cresol novolac epoxy resin.
9. The use of an active ester resin containing epoxy groups according to claim 7 in the preparation of a high-toughness, high-heat-resistant, low-dielectric copper-clad laminate, characterized in that: The bismaleimide resin is a compound having maleimide rings at both ends.
10. Use of an active ester resin containing epoxy groups according to claim 9 in preparing a high-toughness, high-heat-resistant, low-dielectric copper-clad laminate, characterized in that: The bismaleimide resin is any one of bis(3-ethyl-5-methyl-4-maleimidophenyl)methane, bis(3,5-diethyl-4-maleimidophenyl)methane, bis(4-maleimidophenyl)methane, bis(3,5-dimethyl-4-maleimidophenyl)methane, 2,2'-bis[4-(4-maleimidophenoxy)phenyl]propane, diphenylmethane bismaleimide, and 2,2'-N,N'-m-phenylene bismaleimide.
Citation Information
Patent Citations
Active ester type imide resin with main chain containing allyl as well as preparation method and application of active ester type imide resin
CN118479996A